(untitled) (Eurasian Journal of Philology Science and Education, 2016)
This article describes the peculiarities of the Kazakh language affixes, including suffixes forming variants of names (nouns, adjectives, numerals), is determined their innovative model. The problem of variability of modern Kazakh language belongs to one of the most important branches of linguistics. Language is closely connected with the community and has a historical nature. In the theory of word formation the problem of variants takes a great place. The subject of language variability, conditions and causes, the direction of development and its influence on vocabulary are particularly relevant to society, as variants of words enrich it. Through variability can be seen at what level is the development of each language, how it (the language) is perfect and flexible. Of course, the study of word options is one of the urgent problems of speech culture in the modern Kazakh language.